2015
DOI: 10.1111/ffe.12352
|View full text |Cite
|
Sign up to set email alerts
|

Research on fatigue crack propagation behaviour of 4003 ferritic stainless steel based on infrared thermography

Abstract: A B S T R A C T Fatigue crack propagation (FCP) behaviour of 4003 ferritic stainless steel was investigated using infrared thermography. Four stages of superficial temperature evolution were observed during the FCP tests: an initial temperature decrease stage, a temperature equilibrium stage, a slow temperature increase stage and an abrupt temperature increase stage; a thermal model is developed to explain the observed temperature evolution. The experimental results indicate that: when the range of stress inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thermodynamic analysis of fatigue process may relate to, for example, estimation of the dissipated energy, 28,29 analysis of heat dissipation sources in fatigue tests, [30][31][32] energy balance, 33 entropy of fatigue process, 34,35 often together with other experimental methods [36][37][38] and fatigue crack propagation. 39,40 Crupi et al 41 showed that the temperature increment and hysteresis loop of the materials are closely correlated because they are both a manifestation of the energy dissipation process in metals under fatigue loading. Much attention is devoted to analyses related to phenomena taking place in the materials during the fatigue loadings.…”
Section: State-of-the-art Analysismentioning
confidence: 99%
“…Thermodynamic analysis of fatigue process may relate to, for example, estimation of the dissipated energy, 28,29 analysis of heat dissipation sources in fatigue tests, [30][31][32] energy balance, 33 entropy of fatigue process, 34,35 often together with other experimental methods [36][37][38] and fatigue crack propagation. 39,40 Crupi et al 41 showed that the temperature increment and hysteresis loop of the materials are closely correlated because they are both a manifestation of the energy dissipation process in metals under fatigue loading. Much attention is devoted to analyses related to phenomena taking place in the materials during the fatigue loadings.…”
Section: State-of-the-art Analysismentioning
confidence: 99%
“…1 Once microcracks occur in these structures, they will continue to expand until the structures fail under alternating loads. 2 Therefore, microcracks have become a serious concern as they pose a great threat to the safety of such structures in polar regions.…”
Section: Introductionmentioning
confidence: 99%